Effect of age and feeding area on meat quality of wild boars. Issue 3 (3rd July 2017) - Pedrazzoli, Martina; Dal Bosco, Alessandro; Castellini, Cesare; Ranucci, David; Mattioli, Simona; Pauselli, Mariano; Roscini, Valentina
Abstract: The stomach content and samples of Longissimus dorsi muscle of 32 feral wild boars were collected in two different feeding areas (forest and farmland) of Umbria region (Italy). The animals from each feeding area were divided into two age classes: class 1 (12–24 months of age; 48 kg average weight) and class 2 (animals older than 2 years of age; 84 kg average weight). The major food categories consumed were hard mast and crops (89.02–75.98%). The L*(lightness) and a*(red to green colour) values of the meat were affected by the feeding area as well as the b*(yellow colour) value; the age significantly affected only the a* and the b* value of the meat. The α-tocopherol was the most abundant vitamin E homologue, ranged between 520.63 and 1881.33 ng/g and was higher in farmland areas. The index of lipid oxidation (TBARS) ranged from 0.093 and 0.140 mg MDA/kg and was higher in wild boars from farmland. The monounsaturated fatty acids (MUFA) ranged between 38.36 and 46.75% and were higher in wild boar of class 2. The total polyunsaturated fatty acids (PUFA) as well as PUFAn-6 were affected by age, while PUFAn-3 was only affected by feeding area and ranged from 0.91 and 1.99 in farmland and forest, respectively. The feeding area affects the intramuscular fat contents in terms of nutritional characteristics of the meat: the n-6/n-3 ratio that was lower in meat from animals hunted in the forest area ( p  ≤ .001), as well as the ARA/(EPA + DHA) ratio ( p  ≤ .01).